Some Properties of Magnetized Bonnor-Dihole Solution in Brans-Dicke Theory - DELİCE, ÖZGÜR (AMER INST PHYSICS, 2017)
Soule properties of magnetized Bonnor-dihole solution in Brans Dicke(BD) theory is discussed. Conical deficit angle and equatiorial geodesics of (jawlike and null particles are investigated in detail for different values of the parameters of the BD solution.